Enzymatically Active and Inactive Phosphodiesterases and Diguanylate Cyclases Are Involved in Regulation of Motility or Sessility in Escherichia coli CFT073 - Rachel R. Spurbeck (American Society for Microbiology, 2012)
ABSTRACT Intracellular concentration of cyclic diguanylate monophosphate (c-di-GMP), a second messenger molecule, is regulated in bacteria by diguanylate cyclases (DGCs) (synthesizing c-di-GMP) and phosphodiesterases (PDEs) (degrading c-di-GMP). c-di-GMP concentration ([c-di-GMP]) affects motility and sessility in a reciprocal fashion; high [c-di-GMP] typically inhibits motility and promotes sessility. A c-di-GMP sensor domain, PilZ, also regulates motility and sessility. Uropathogenic Escherichia coli regulates these processes during infection; motility is necessary for ascending the urinary tract, while sessility is essential for colonization of anatomical sites. Here, we constructed and screened 32 mutants containing deletions of genes encoding each PDE (n = 11), DGC (n = 13), PilZ (n = 2), and both PDE and DGC (n = 6) domains for defects in motility, biofilm formation, and adherence for the prototypical pyelonephritis isolate E. coli CFT073. Three of 32 mutations affected motility, all of which were in genes encoding enzymatically inactive PDEs. Four PDEs, eight DGCs, four PDE/DGCs, and one PilZ regulated biofilm formation in a medium-specific manner. Adherence to bladder epithelial cells was regulated by [c-di-GMP]. Four PDEs, one DGC, and three PDE/DGCs repress adherence and four DGCs and one PDE/DGC stimulate adherence. Thus, specific effectors of [c-di-GMP] and catalytically inactive DGCs and PDEs regulate adherence and motility in uropathogenic E. coli. IMPORTANCE Uropathogenic Escherichia coli (UPEC) contains several genes annotated as encoding enzymes that increase or decrease the abundance of the second messenger molecule, c-di-GMP. While this class of enzymes has been studied in an E. coli K-12 lab strain, these proteins have not been comprehensively examined in UPEC. UPEC utilizes both swimming motility and adherence to colonize and ascend the urinary tract; both of these processes are hypothesized to be regulated by the concentration of c-di-GMP. Here, for the first time, in a uropathogenic strain, E. coli CFT073, we have characterized mutants lacking each protein and demonstrated that the uropathogen has diverged from E. coli K-12 to utilize these enzymes to regulate adherence and motility by distinct mechanisms.